Degradation Of Oxytetracycline From Aquaculture Wastewater Using Sole Ozonation And Catalytic Ozonation In The Presence Of Activated Carbon - Murthi, Bohesharvind Naraiyanan (Universiti Sains Malaysia, 2022)
Advanced oxidation processes, such as ozonation, are gaining attention due to their capability to degrade antibiotics. However, generation of ozone is known to be an energy intensive process and greatly affected by the surrounding conditions. Hence, the efficiency of sole ozonation and catalytic ozonation to treat synthetic aquaculture wastewater containing oxytetracycline was studied. Throughout the experiment, the ozone flowrate was held constant at 500 mg/h and the sole ozonation was carried out for 120 minutes while catalytic ozonation was carried out for 60 minutes. Factors affecting the process including the effect of temperature (13℃, 23℃,33℃), initial pH (3, 5, 7, 9, 11), initial concentration of oxytetracycline solution (10 mg/L, 30 mg/L, 50 mg/L) and initial activated carbon dosage (75mg/L, 125 mg/L, 175mg/L, 225mg/L, 275mg/L) was studied. The pH 9 (slightly alkaline) achieved the optimum degradation efficiency of 91.2% within 60 minutes of ozonation. In this pH condition, more hydroxyl radicals and ozone reacted with oxytetracycline without being damaged by hydroxyl radical scavengers. The optimum temperature was found to be 23 ℃ with a degradation efficiency of 88.5% as it provided a good balance for the opposing effect between the rate of ozonation and solubility of ozone in aqueous solution. The oxytetracycline degradation decreased with the increase in initial oxytetracycline concentration due insufficient ozone supply. The degradation efficiency increased with the increase in activated carbon dosage as more specific sites were available. The optimum activated carbon dosage was found to be 225 mg/L as it gave the highest degradation of oxytetracycline (98.6%). However, further increase in activated carbon dosage up to 275 mg/L resulted in similar degradation efficiency (99.2%) due to the saturation of specific site of activated carbon. The antibiotic kinetic analysis shows that the sole ozonation of the oxytetracycline follows the first order reaction for the first 60 minutes while second order reaction for total reaction time of 120 minutes. The catalytic ozonation showed a better degradation than sole ozonation in just 30 minutes. For instance, the oxytetracycline degradation efficiency for catalytic ozonation and sole ozonation were 98.6% and 73.0%, respectively. In a nutshell, catalytic ozonation was proven to be much more effective than sole ozonation.